Dynamic Constitutive Properties and Modelling of Geopolymer Concrete and Fibre Reinforced Geopolymer Concrete - Chen, Chong (Curtin University, 2023)
This thesis assesses the suitability of dynamic constitutive models for Portland-cement concrete in accurately modelling the dynamic response of Geopolymer Concrete (GPC) structures, validated against existing test data. It quantifies the mechanical properties of GPC and Fibre Reinforced GPC (FR-GPC), developing appropriate models for simulating the dynamic behaviours of related RC structures. The responses of such structures are systematically investigated, providing empirical design formulas for practical engineering applications.